2007
DOI: 10.1038/sj.bjc.6603789
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of pathogenic mechanisms in multiple colorectal adenoma patients without germline APC or MYH/MUTYH mutations

Abstract: Patients with multiple (5 -100) colorectal adenomas (MCRAs) often have no germline mutation in known predisposition genes, but probably have a genetic origin. We collected a set of 25 MCRA patients with no detectable germline mutation in APC, MYH/MUTYH or the mismatch repair genes. Extracolonic tumours were absent in these cases. No vertical transmission of the MCRA phenotype was found. Based on the precedent of MYH-associated polyposis (MAP), we searched for a mutational signature in 241 adenomatous polyps fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
20
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 17 publications
4
20
1
Order By: Relevance
“…This finding is similar to two other reports of MCRA (7, 8) with patients diagnosed at ages 50 and 60 years old. In our cohort, colorectal cancer screening guidelines appeared to influence the age of diagnosis since the majority of patients were diagnosed at screening colonoscopy.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is similar to two other reports of MCRA (7, 8) with patients diagnosed at ages 50 and 60 years old. In our cohort, colorectal cancer screening guidelines appeared to influence the age of diagnosis since the majority of patients were diagnosed at screening colonoscopy.…”
Section: Discussionsupporting
confidence: 92%
“…Most efforts have focused on the identification of germline mutations that affect DNA mismatch repair genes (hMLH-1, hMSH-2, hMSH-6, hMSH-3, PMS-2), MYH/MUTYH, and APC, all of which are associated with increased numbers of colorectal adenomas and significantly increased colorectal cancer risk. 14,33,40,[44][45][46][47][48] However, our results and those of others indicate that most patients <40 years of age lack evidence of an underlying polyposis disorder and other predisposing factors. 27 The combined results of 2 reports, which evaluated 73 patients <40 years of age, found that only 4% had familial adenomatous polyposis, HNPCC, or inflammatory bowel disease, and 8% had a family history of colorectal carcinoma.…”
Section: Discussioncontrasting
confidence: 80%
“…The clinical and family characteristics of the participants are consistent with published data from other mutation-negative polyposis cohorts. 14; 15; 19; 55 Using this approach, we identified two families with biallelic LoF germline mutations in the MMR gene MSH3, a genotype which has not yet been described as causative for a polyposis phenotype. In addition, we found one individual with biallelic PMS2 mutations, and several persons who harbored homo- and heterozygous LoF variants.…”
Section: Discussionmentioning
confidence: 99%